Kinematic-Based Modeling of Shear-Dominated Concrete Walls with Rectangular and Barbell Sections. Issue 7 (7th June 2021) - Tatar, Nikola; Mihaylov, Boyan
ABSTRACT: In this paper, the complete behavior of shear-dominated reinforced concrete walls is studied with a three-parameter kinematic theory (3PKT), a rational and efficient approach based on a three-degree-of-freedom description of the deformation patterns in walls. The paper summarizes the original 3PKT method for rectangular sections and extends it to account for the effects of barbells, strain penetration in the foundation, cracking above the critical shear cracks, and stirrup ruptures. It is shown that the 3PKT captures adequately the local and global response of shear-dominated walls, including the complete displacement field and the width of the critical shear cracks.